CONCEPTION RATE DAN SERVICE PER CONCEPTION PADA SAPI BALI HASIL INSEMINASI BUATAN DI KABUPATEN SUMBAWA BARAT TAHUN 2017 - Deskayanti, Asih; Sardjito, Trilas; Sunarso, Agus; Srianto, Pudji; Suprayogi, Tri Wahyu; Hermadi, Herry Agoes (Universitas Airlangga, 2019)
The study was conducted to know Conception Rate and Service per Conception of Bali cattle acceptors in west Sumbaw district. Data were collected fot the periode of January to September 2017 from inseminator in west Sumbawa district. The data were taken by primary and secondary data. Primary data retrieval is done by direct observation, which includes several variables, where the variable include the identitiy of the breeder, the cages, feeding, drinking and knowladge of breeders. The secondary data were obtained by recording of the officer insemination. All data was analyzed to find a percentage of Conception Rate and find number of Service per Conception (S/C) by analyzed descriptive of SPSS. Risults of this research showed that Conception Rate and Service per Conception's average of Bali Cattle is 60 % and 1,7. The conculusion of this research showed that Conception Rate is lower than normal value and Service per Conception of Bali cattle in West Sumbawa district is better. This research was expected to be a reference for the next artificial insemination programmed by the government.